One Drop Improves Productivity for Workers With Type 2 Diabetes: One Drop for Workers With Type 2 Diabetes. Issue 8 (11th August 2022) - Lavaysse, Lindsey M.; Imrisek, Steven D.; Lee, Matthew; Osborn, Chandra Y.; Hirsch, Ashley; Hoy-Rosas, Jamillah; Nagra, Harpreet; Goldner, Dan; Dachis, Jeff; Sears, Lindsay E.
Abstract : Improving diabetes management skills and reducing diabetes-related distress in working adults with type 2 diabetes has implications for work-related outcomes including work productivity. Digital health programs have the potential to positively impact diabetes management and, in turn, improve the productivity of working-age adults. Abstract : Objective: Diabetes research on work productivity has been largely cross-sectional and retrospective, with only one known randomized controlled trial (RCT) published, to our knowledge. Secondary analysis of the Fit-One RCT tested the effect of One Drop's digital health program on workplace productivity outcomes, absenteeism, and presenteeism, for employees and specifically for older workers with type 2 diabetes. Methods: Analysis of the 3-month Fit-One trial data from employees who have type 2 diabetes explored productivity using logistic analyses and generalized estimating equations. Results: Treatment and control group comparisons showed that workers ( N = 125) using One Drop see direct benefits to workplace productivity, which leads to productivity savings for employers. Conclusion: This was the first RCT to demonstrate that a mobile health application for managing type 2 diabetes can positively affect productivity at work.